(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The study problematized language ideologies and policy to explore the efficacy of using English as the Language of Learning and Teaching (LOLT) among Oshiwambo speaking learners in the Omusati region of Northern Namibia. Focus group interviews with ESL teachers, interviews with the English Head of Departments (HODs), classroom observations and informal chats with the grade 12 learners were carried out at six secondary schools. The study finds that students struggle to partake in meaningful classroom interaction and to comprehend instruction and content in English. Although students may express themselves better in Oshiwambo, they are not allowed. Some ESL teachers would use Oshiwambo to maintain order in class, but avoid using Oshiwambo to help struggling learners believing this would negatively impact learners’ English proficiency. Some ESL teachers were also found to blame ESL content subject teachers for learners’ poor English proficiency, as they used Oshiwambo in class to teach and explain content. We conclude that ESL classroom practice is teacher-centred by default, and students are muted as they find themselves with no voice to express themselves efficiently and efficaciously, and deaf to classroom content delivered in an unfamiliar language, English.